ANTECEDENTS AND CONSEQUENCES OF CAREER DEVELOPMENT OF EMPLOYEES IN BAPERLITBANG KARIMUN REGENCY - Sawaluddin Sawaluddin; Indrayani Indrayani; Muammar Khaddafi; Ngaliman Ngaliman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to see the influence of career development of civil servants in the Planning, Research, and Development Agency of Karimun Regency. The number of respondents used as samples in this study was as many as 65 people. The results showed that: (1) Education has a significant effect on career development, Education has a significant effect on Job Promotion, (2) Training does not significantly affect the Promotion of Positions, (3) Promotion of Positions has a significant effect on career development, (4) Mutations have a significant effect on the Promotion of Positions, (5) Mutations have a significant effect on the career development of employees in the office of the Planning, Research and Development Agency of karimun district.